(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
erive meaningful insights through Big Data. With emerging technology, Machine Learning can now be used to predict almost any result according to any functionality. Machine Learning studies underlying patterns in the data and thus derives a suitable model. Medical Sciences face new challenges every day for example, illiteracy in patients about the actual diseases they are facing, taking further steps in treatments, medications needed to treat diseases and so on. This project will help patients to detect cancer and guide patients to proceed with the correct treatments through the mere input of symptoms faced, medical histories if any, current medical reports like blood, pathology, heart, ECG, etc. The model will thus be able to represent itself just how a doctor can, to patients.